Image Authentication Proofing Scheme Based on RLG by Employing the Characteristics of DCT - Ghozzi, Fahmi; Jabbar, Khalid Kadhim; Fakhfakh, Ahmad (Iraqi Journal of Science, 2025)
The impetus behind the emergence of information security was the need to send sensitive data over the often insecure Internet networks. Information and communication technology fields have used authentication to verify alleged users identities and prevent intruders from achieving their goals. However, with the increasing use of digital images in multimedia applications, particularly those requiring high levels of security, there has been a growing interest in ways to ensure their safety. A secret key was generated randomly to add to the proposed encryption system, increasing its complexity to preserve privacy and reduce the influence of intruders. Our method uses a reversible logical approach for security and privacy based on discrete cosine transforms (DCT) to propose a semi-fragile watermark approach to detect and locate any changes. The results show a high degree of accuracy in verifying and establishing the color image’s reliability, all while maintaining image quality during the embedding and retrieval phases. Results showed that the proposed method is very good at finding and locating any manipulation by the intruder on the colored image while maintaining the image quality after the embedding process.